Employment and human capital investment intentions among recent refugees in Germany - Peter Haan; Martin Kroh; Kent Troutman (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Motivations to participate in the labour market as well as to invest in labour market skills are crucial for the successful integration of refugees. In this paper we use a unique dataset - the IAB-BAMF-SOEP Refugee Survey, which is a representative longitudinal study of all refugees reported on administrative records in Germany - and analyse which determinants and characteristics are correlated with high motivation and intention to participate in the labour market. We find that overall men have a strong intention to work and to invest in human capital. The result for women is different: among women, having children, lack of German language skills, and having no previous work experience significantly and consistently correlate with lower expectations and intentions of future economic integration. Furthermore, we find a significant relationship between the degree of traditional or patriarchal views of women's societal roles, and our corresponding outcomes of interest.
Keywords: F22; J22; J24; 330; refugees; labor market integration; human capital investment